(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
We analyzed the development of hearing loss factors in newborns. In pediatric cases, the collection of anamnesis is crucial for the early diagnosis of hearing loss. This anamnesis includes questions concerning the perinatal anamnesis of the child, his birth and the first days of life, as well as the postpartum anamnesis before the onset of symptoms, as well as the family history of hearing loss.